Tailorable magnetocaloric effect by Fe substitution in Gd-(Co, Fe) amorphous alloy. (August 2019) - Zhang, Ziyang; Tang, Qin; Wang, Fachao; Zhang, Huiyan; Zhou, Yuxin; Xia, Ailin; Li, Hailing; Chen, Shuangshuang; Li, Weihuo
Abstract: The magnetocaloric properties of Gd70 Co30- x Fe x ( x  = 0, 5, 10) amorphous ribbons were measured, analyzed and compared with the reported experimental data of Gd50 Co50- x Fe x ( x  = 0, 2, 5) and Gd60 Co40- x Fe x ( x  = 0, 5, 10) amorphous alloy series. The results show that the magnetocaloric effect (MCE) of Gd-(Co, Fe) amorphous alloys could be tuned on the basis of following mechanism: the magnetic transition temperature ( T C ) of the Gd-(Co, Fe) amorphous alloys linearly increases about 22 ± 2 K with every substitution of 5 at% Fe for Co, and the maximum magnetic entropy change |Δ S M pk | of each alloy series nearly linearly depends on the T C −2/3 . Additionally, the Gd-(Co, Fe) amorphous alloys with higher Fe content exhibit the table-like MCE and higher value of exponent n ( T pk ) ( | Δ S M p k | ∝ H n ( T p k ) ). Highlights: The Gd70 Co30- x Fe x ( x  = 0, 5, 10) amorphous ribbons were produced. The adjustable magnetocaloric effect of Gd-(Co, Fe) amorphous alloys were studied. Every 5 at% replacement of Fe may raise the Curie temperature ( T C ) by ∼22 ± 2 K. The correlation of magnetic entropy change peak with T C −2/3 is nearly linear. The table-like curves obtained in the Gd-(Co, Fe) alloys with higher Fe content.